Analysis of Factors That Affect Cost Consciousness in Non-Profit Organizations - Doddy Hapsoro; MARIA ELLY BUDIARTI (The Indonesian Journal of Accounting Research, 2013)
The aim of this study is to examine the effect of formal authority structure,accounting information characteristics, work motivation and informal authoritystructure on cost consciousness mediated with manager behavior for decisioncontrol and decision management. The result of this study contributes to theorydevelopment, particularly with regard to behavioral accounting, and also contributesto managerial practices in improving expense effectiveness and efficiencythrough cost conscious behavior. The data of this study were taken from a nonprofit organization that provides educational services. The questionnaires weredistributed to middle managers and structural officers at the educational institutions.The data were collected by a contact person. There were 250 questionnairessent to respondents with a 62.8 percent response rate. Analysis was conducted byusing the Two Step Approach of the SEM technique with Amos. The result showsthat formal authority structure has been proven to positively affect manager behaviorin decision control and decision management. Accounting informationcharacteristics have a positive effect on manager behavior in decision control anddecision management. Work motivation is not shown to positively affect managerbehavior in decision control and decision management. Informal authority structureproved to positively affect manager behavior in decision control and decisionmanagement. Decision control and decision management proved to positively affectcost consciousness. Formal authority structure and informal authority structurehas not been proven to positively affect cost consciousness